2013
DOI: 10.3892/ijmm.2013.1584
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of P-glycoprotein in peripheral blood CD8+ T lymphocytes from HIV-1-infected patients on antiretroviral therapy

Abstract: In this study, we aimed to measure P-glycoprotein (P-gp) expression in CD8(+) T lymphocytes of HIV-1-infected patients, to investigate how P-gp levels are affected by antiretroviral therapy (ART) in HIV-1 infection, and to assess the value of using P-gp expression to predict virologic response to ART. Peripheral blood mononuclear cells (PBMCs) were obtained from a cohort of HIV-1‑infected patients in China: 140 patients on ART, and 49 ART-naïve patients. We also enrolled 24 healthy blood donors as the controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…89 In contrast, the increased MDR1 expression at transcriptomic and protein levels detected on CD8 + T cells in treated patients is associated with a better efflux capacity. 90 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…89 In contrast, the increased MDR1 expression at transcriptomic and protein levels detected on CD8 + T cells in treated patients is associated with a better efflux capacity. 90 …”
Section: Introductionmentioning
confidence: 99%
“…The hostile tumor micro-environment and its chemical composition must indeed shape the immune infiltrate, and MDR1 expression by anti-tumor immune cells may favor their preservation despite harsh environmental conditions. The immune infiltrate is also modulated by MDR1-associated anti-neoplastic agents, 90,101 and evaluation of MDR1 level on immune cells could be an indicator of these treatments’ effects.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, various pharmacological formulations of ARVs have been tested vaginally or orally for a pre-exposure prophylaxis of HIV-1 in women, but the presence of P-gp significantly diminishes the efficacy of the administered ARV [43]. Finally, P-gp can be highly overexpressed in response to therapy administration, as well documented by studies on CD8+ T lymphocytes isolated from the peripheral blood of HIV-1-infected patients under ARV treatment [44]. In conclusion, P-gp system plays a crucial role in preventing the penetration of ARVs into HS, and overcoming this barrier is of primary importance for proper viral eradication.…”
Section: The P-glycoprotein: a Molecular Barrier To Arvsmentioning
confidence: 99%
“…Currently, several new drug discovery projects have an array of novel pro-drug compounds in pipeline to bypass or exert a more sustained P-gp inhibition (11). Interestingly, over the past two and half decade accumulating evidence suggested that the expression of P-gp in inflammatory immune cell subset (12)(13)(14)(15). This could exert a potential anti-cancer cytotoxic functionality.…”
Section: Introductionmentioning
confidence: 99%